A new antiviral 14-nordrimane sesquiterpenoid from an endophytic fungus Phoma sp. (February 2019) - Liu, Si-Si; Jiang, Ju-Xing; Huang, Rong; Wang, Ya-Ting; Jiang, Bo-Guang; Zheng, Kai-Xuan; Wu, Shao-Hua
Graphical abstract: Highlights: A new rare 14-nordrimane sesquiterpenoid was isolated from endophytic Phoma sp. The structure was elucidated by means of spectroscopic methods. Compounds1 and2 exhibited antiviral activity against H1N1 influenza virus. Abstract: A new rare 14-nordrimane-type sesquiterpenoid, named phomanolide (1 ), together with five known compounds, (–)-6-methoxymellein (2 ), 7-hydroxy-3, 5-dimethyl-isochromen-1-one (3 ), norlichexanthone (4 ), 6-methylsalicylic acid (5 ), and gentisyl alcohol (6 ), were obtained from the culture broth of an endophytic fungus Phoma sp. isolated from the roots of Aconitum vilmorinianum . The structure of compound1 was established based on extensive spectroscopic analysis. Compound1 was the first example of 14-nordrimane-type sesquiterpene up to now. Compounds1 and2 showed antiviral activities against influenza A virus (A/Puerto Rico/8/34, H1N1) with IC50 values of 2.96 ± 0.64 and 20.98 ± 2.66 μg/mL, respectively.